Sacred Chants on Stage: The Performative Reconstruction of Yushan Fanbai - Chai, Yutong (Pacific International Journal, 2025)
This paper examines the transformative journey of Yushan Fanbai, a traditional Chinese Buddhist chant, as it transitions from monastic ritual to staged performance. Originally embedded in liturgical practice where sound served spiritual discipline rather than artistic display, Fanbai has entered new domains of cultural presentation through intangible cultural heritage policies and spiritual-aesthetic markets. Analyzing its performative reconstruction, this study identifies how Fanbai’s sonic, bodily, and spatial dimensions are systematically reconfigured for theatrical settings. Ritual chanting is reshaped into melodic phrases with harmonic enrichment; restrained bodily composure becomes choreographed movement; and sacred space gives way to symbolic scenography. These adaptations are driven externally by heritage frameworks and media markets, and internally by monastic communities seeking cultural outreach and institutional legitimacy. The resulting performance exists in a liminal space between ritual authenticity and aesthetic communication, generating tensions regarding sacredness and mediation. Ultimately, this reconstruction reflects not the dilution of tradition but its dynamic rearticulation, demonstrating how religious practices negotiate continuity within contemporary cultural economies while offering insights into the broader evolution of intangible cultural heritage in modern China.